https://doi.org/10.36873/agp.v20: UJI MUTU BENIH TIGA VARIETAS PADI (Oriza sativa L) PADA BEBERAPA WADAH SIMPAN The test quality seed of tree rice variety on the several storage containers, Suparto, H.*1), Widyawati, W.,2) dan Nurlaila2) - Admin journal (Fakultas Pertanian Universitas Palangka Raya, 2019)
ABSTRACTThe aim of the study was to examine several storage containers for the quality of the seeds of threerice varieties. Using a randomized block design faktorial. The first factor is the storage container (W)consisting of W1 = open cardboard, W2 = gunny sack, W3 = plastic and W4 = can. The second factor isrice varieties consisting of V1 = inpara 3, V2 = situbagendit and V3 = towuti. The physiological qualityvariables observed are water content, germination power and the potential for maximum seed growth.The results showed that the storage container and variety had an effect on water content, germinationand the potential for maximum seed growth. The physiological quality of Towuti seeds can bemaintained for up to 70 days in a sealed storage container in the form of cans.Keywords: seeds, rice variety and storage container